Manajemen Peningkatkan Mutu di Sekolah Menengah Atas Negeri 1 Pecangaan Kabupaten Jepara - Murtadlo, Khusnull; Ysh, AY Soegeng; Maryanto, Maryanto (PGRI Kota Semarang, 2024)
Abstract The educational process will be of quality if all educational components are involved in the educational process. These educational components include educational objectives, students, educators, educational methods, educational content, educational environment, and educational tools and facilities. The focus of the research is to describe and analyze the role of the principal in improving academic quality at SMA N 1 Pecangaan, Jepara Regency. The research approach used is qualitative. This type of research is a case study. Qualitative research design through data condensation, presenting data (data display), and drawing conclusions or verification (conclusion drawing and verification). Data collection techniques are interviews, observation and documentation. This research uses triangulation of sources and methods. Data analysis in three steps: data reduction, presenting data, and drawing conclusions. The results of the research show that: (1) the quality improvement management planning carried out by the school principal includes identifying needs and socializing school programs. (2) organizing quality improvement management carried out by the school principal includes the placement of school resources, organizational development, assignment and delegation of authority. (3) the implementation of quality improvement management carried out by the school principal includes implementing school quality improvement and implementing academic supervision. (4) supervision of quality improvement management carried out by the school principal including evaluation of school activities and solutions to activity constraints. The author suggests continuing to build effective communication with school members, building teamwork and making continuous and sustainable improvements. Teachers are required to always be ready and supportive in carrying out activities. Keywords: School Quality Improvement Management